Spatial distribution of economic activities and transboundary pollutions. (7th January 2015) - Ciucci, Julien; Prunetti, Dominique; Maupertuis, Marie–Antoinette
Different empirical studies confirm that individuals consider environmental quality in their location choices. Nonetheless, little attention has been devoted to the role of transboundary pollution in the agglomeration or spreading of economic activities. This contribution introduces transboundary pollution in the field of new economic geography providing an extension of Ottaviano's core–periphery model (Ottaviano, 2001). In terms of long run equilibria, the introduction of pollution into the footloose entrepreneur model has two major consequences. First, it allows several original equilibrium configurations, which do not arise by considering only transport costs. Secondly, for a given level of transport cost, different equilibrium configurations may occur, depending on the environmental parameters.